An occupational therapy actuation proposal for children and adolescents care developed at the "Fundação Cidade Mãe" - Pimentel, Adriana Miranda (Revista de Terapia Ocupacional da Universidade de São Paulo, 2000)
This article is about a project which has being developed in the field of education, between the graduation course of Occupational Therapy of the "Escola Baiana de Medicina e Saúde Pública" and the "unidades" of the "Fundação Cidade Mãe". It weans to describe (show) na experience which in happening among the organizations which deal with children and adolescents care in Salvador and the possibility of Occupational Therapy intervention (actuation).